Management of drug-induced movement disorders in psychiatry: an update - Sekh Afrar Alam; Aparajeeta Baruah; Gopal Agarwal; Nilesh Mohite (Open Journal of Psychiatry and Allied Sciences, 2016)
Drug-induced movement disorders (DIMD) represent a variety of iatrogenic and clinically distinct movement disorders, including akathisia, tardive dyskinesia, dystonia, and Parkinsonism. DIMD remain a significant burden especially among certain patient populations receiving psychotropic medication. Knowledge of DIMDs will allow clinicians and healthcare professionals to better identify and manage patients with these conditions. Here we discuss the important features and current practical management steps of different types of DIMD in psychiatry.